Break Even Point Analysis as A Profit Planning Tool at PT. Herbal Medicine and Pharmaceutical Industry Sido Muncul Tbk - Septiani, Arin Adelia; Djuwita, Diana; Usman, Usman (Wealth: Journal of Islamic Banking and Finance, 2024)
One of the tools used in profit analysis planning is break even point analysis. Break even point analysis is an analysis to determine the break even point, namely the situation where a company does not make a profit and does not experience losses. This research aims to determine the level of break even point, contribution margin, margin of safety and profit targets achieved, as well as to find out whether the break even method is effectively used for profit planning. This research uses quantitative descriptive methods. The type and source of data used is secondary data in the form of the official financial report of PT Sido Muncul for the 2020-2022 period. The data analysis techniques used are break even point analysis, contribution margin, margin of safety and profit target. The results of this research show that the company's condition is very good because it has exceeded the company's break even point, so that the company makes a profit or profitability. The results of the margin of safety calculation also show that the safety limit of PT Industri Jamu and Farmasi Sido Muncul is classified as safe, because the sales figure has exceeded the calculated value of the margin safety